A Study on the Effect of Housing on Haematological Parameters of Nellore Lambs (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect of housing on haematological parameters of Nellore  Jodipi lambs. Thirty weaned Nellore ram lambs of 3-4 months age were divided into three groups of  ten each. The lambs in Group-I were housed with morum flooring and asbestos roofing with tree  shade, while Group-II lambs were housed with morum flooring and asbestos roofing without tree  shade and Group-III lambs were housed with elevated slatted flooring and galvalume roofing without  tree shade. Temperature and humidity values were significantly (P
Keywords: Nellore Jodipi lambs; housing, haematological parameters; slatted flooring